SUITABILITY OF NIGERIAN CORN HUSK AND PLANTAIN STALK FOR PULP AND PAPER PRODUCTION - Aremu, M. O.; Aperolola, S. O.; Dabonyan, O. O. (European Scientific Journal, ESJ, 2015)
Wood is a prominent raw material in the production of pulp and paper, but due to the impact of forest depletion on the environment worldwide, research is being focused on non-wood sources as alternative sources of fibre and as a solution to destruction of the environment. The aim of this study therefore, is to investigate the suitability or otherwise of corn husk and plantain stalk which are abundant agro-waste materials in Nigerian environment in pulp and paper production. The pulping of corn husk and plantain stalk was achieved through Chemical Pulping process (Soda pulping) and the pulps obtained were analyzed for their chemical compositions. Also, the scanning electron microscopy (SEM) was used to analyze the surface morphological structure of the pulps produced. The resulting pulps were then used for papermaking and the Mechanical strength of papers obtained was determined. The results of chemical composition analysis for the pulp obtained from corn husk were (3.57%, 41.23%, 10%, 12.04% and 23.00 %) while that of plantain stalk were (11.19%, 57.86%, 10%, 4.60% and 35.96%) for Ash content, Cellulose content, Moisture content, Lignin content and Pulp yield respectively. The result of Mechanical strength analysis of the paper produced are (66.04 g/m2, 0.30 mm,5.33 Nm/g,12.83Nm2/g,0.13 N/mm2,2.7 mm) from corn husk while that of plantain stalk are (30.99 g/m2,0.08 mm,1.25 Nm/g,5.20Nm2/g,2.95 N/mm2,2.20 mm) for Grammage, Thickness, Tensile index, Tear index, Modulus of Elasticity and Elongation at break respectively. The SEM images analysis showed that there is a more condensed and packed arrangement of fibre in corn husk than plantain stalk. The overall results showed that Corn husk and Plantain stalk have a promising potential as alternative source of fibre in paper making industry.